COMPARATIVE STUDY OF HISTOPATHOLOGICAL CHANGES BETWEEN NANO-BORON AND BORON IN SMALL INTESTINE OF LAYER CHICKENS - Abtisam J. A.,; A. Q. Al-Awadi,; B. H. Ali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of this study was to compare the effect of boron and nanoboron" on histomorphology of the small intestine in layer chickens. 210 day-old chicks were used and were randomly assigned to seven equal groups.  The experiment, groups were exposed to both normal boron and nano-boron as follows:G1 received 15 mg/L of boron in their drinking water, G2 got 25 mg/L, G3 got 45 mg/L, while groups nano boron as following G4 got 15 mg/L, G5 got 25 mg/L, G6 got 45 mg/L of nano-boron, and G7 was not given any treatment. By using a light microscope, the  histomorphology result of intestine was  examine to determine the villi's height, thickness, crypt depth, and muscle thickness. The measurements of villi height, crypt depth, and muscle thickness showed a significant difference (P≤0.05) between all treated groups (nanoboron at G5,G6 than  normal boron) in comparison with  control group, with the highest mean in G6(NB) in all measures of intestine. The findings of this study concluded that the adding of "boron and nanoboron" to consumption water improved the structure of intestine, and this was particularly evident at high nanoboron concentrations.